ANÁLISE COMPARATIVA DO TEMPO DE INTERNAÇÃO E DO TEMPO DE USO DA VENTILAÇÃO MECÂNICA ENTRE IDOSOS E ADULTOS JOVENS (Movimenta (ISSN 1984-4298), 2018)
It is controversial whether age may be a marker for determining length of stay and mechanical ventilation (MV). Objectives: to characterize elderly and young adults in Intensive Care Unit (ICU), to compare the days in hospital and ICU and duration of mechanical ventilation between both groups and determine if there is a relationship between age, length of stay at the hospital and time of mechanical ventilation in the elderly group. Methods: This study is a retrospective chart. A descriptive statistics were proceeded of clinical and demographic measures of the participants, Pearson correlations and t-student test for independent samples. The significance level of .05 was considered. Results: 102 charts were reviewed, 18 young adults (47.72± ± ± ± 9.83 years) and 84 elderly (76.60± ± ± ± 9.68 years).The analysis showed that 61.9% of the elderly and 50% of young adults assessed were female, 32.1% of the elderly and 22.2% of young adults died, 67.9% of the elderly and 77.8% of young adults were discharged. The elderly people had longer hospitalization than young adult in the ward (8.31± ± ± ±6.74 vs 4.61± ± ± ±2.66, p=0.00) and spent more time using MV (4.14±4.57 vs 0.22± ± ± ±0.65, p=0.017). The most common diagnosis for elderly admission was pneumonia (31%), followed by congestive heart failure (CHF) (16.70%), stroke (10.7%) and chronic obstructive pulmonary diasease (COPD) (7.1%), while in young adults prevailed stroke (16.7%), followed by arrhythmia, shock, pneumonia and congestive heart failure (11%). It was found positive correlation between low age and amount of days of hospitalization on ICU (r=0.310, p=0.004). Conclusion: Older people remain more time on MV and hospitalized than younger adults. There is significant relationship between age and length of hospital stay and MV.